Gastric Emptying of Carbohydrate Drinks in Term Parturients Before Elective Cesarean Delivery: An Observational Study. Issue 4 (December 2020) - Popivanov, P.; Irwin, R.; Walsh, M.; Leonard, M.; Tan, T.
Abstract : ( Int J Obstet Anesth . 2020;41:29–34) Most enhanced recovery after surgery programs now opt to use preoperative carbohydrate (CHO) drinks as a standard part of their protocol. Preoperative fasting guidelines set by the American Society of Anesthesiologists (ASA) state that moderate amounts of clear fluids up to 2 hours before anesthesia are allowed for uncomplicated patients undergoing elective surgery. Most research regarding clear liquid consumption before anesthesia has been performed in nonpregnant patients although recent data found gastric emptying of water was not delayed in nonlaboring parturients. The rate of gastric emptying of CHO drinks in a pregnant population has yet to be studied, however. The aim of this study was to investigate gastric emptying of 400 mL of a CHO drink up to 2 hours before elective cesarean delivery.